A synoptical account of the Sterculiaceae in Bangladesh - Rahman, M. Oliur; Hassan, Md. Abul; Mia, Md. Manzurul Kadir; Huq, Ahmed Mozaharul (Bangladesh Journal of Plant Taxonomy, 2012)
Taxonomy, updated nomenclature and occurrence of the species belonging to the family Sterculiaceae in Bangladesh have been presented. Detailed herbarium study at Royal Botanic Gardens, Kew (K), Royal Botanic Garden, Edinburgh (E), British Museum (BM), Bangladesh National Herbarium (DACB) and Dhaka University Salar Khan Herbarium (DUSH) has revealed the occurrence of 32 species under 15 genera of the Sterculiaceae in Bangladesh. The correct name, important synonym(s), salient diagnostic characteristics, specimens examined and distributional notes have been provided for each species. Dichotomous bracketed keys have also been presented for identification of genera and species. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10943 Bangladesh J. Plant Taxon. 19(1): 63-78, 2012 (June)